Tissue Factor Pathway Inhibitor (TFPI) Levels in the Plasma and Urine of Children with Meningococcal Disease - Eling, M.; Stephens, A. C.; Oragui, E. E.; Rivers, R. P. A.; Levin, M. (Thrombosis and Haemostasis, 2001)
Tissue factor pathway inhibitor (TFPI) is a potent inhibitor of the TF-dependent coagulation system. In meningococcal disease, up-regulation of tissue factor expression on blood monocytes and possibly on endothelial cells has the potential to trigger the activation of the TF-dependent pathway of coagulation. Intravascular coagulation is considered to be a major pathogenic factor in meningococcal disease. We postulated that imbalance between TF expression and TFPI concentration might lead to uncontrolled coagulation in meningococcal disease. The aim of this study was to assess the levels of total TFPI in the plasma of patients with meningococcal disease and assess whether increased leaking of the TFPI was occurring. TFPI antigen levels and activity were measured in the plasma of 54 patients with meningococcal disease, and 13 healthy control children. TFPI antigen level were also determined in the urines of 14 of the 54 and 9 healthy control children. Plasma TFPI activity was reduced in the meningococcal diseased patients (mean of 0.503 ± 0.341 U/ml; control, 1.010 ± 0.199 U/ml; p <0.0001), as was the TFPI antigen levels (mean of 54.85 ± 35.05 ng/ ml; Control, 94.51 ± 11.44 ng/ml; p <0.0001). In contrast, TFPI antigen levels were increased in the urine of these patients when compared to the levels found in the urine of the healthy control children (mean of 12.96 ± 5.392 ng/mmol creatinine; Control, 0.239 ± 0.191 ng/mmol creatinine; p <0.035). A lack of correlation between TFPI-activity and TFPI-antigen plasma levels was observed (r = 0.002, p = 0.85). This data is consistent with the hypothesis that in meningococcal disease there is increased inactivation of plasma TFPI by the up regulation of tissue factor expression but in addition increased clearance of TFPI in urine is occurring.
Keywords: Tissue factor pathway inhibitor; meningococcal disease; glycosaminoglycans; capillary leak